Mathematical modelling of the road bumps using laplace transform (2007)
The contribution of this paper to traffic engineering is the application of Laplace Transform to the quantification of speed control in the modelling of road bumps with hollow rectangular shape. The paper simulates the behaviour of a vehicle when passing over a series of bumps. In many countries the current practice used for lowering the vehicle speed is to raise road bumps above the road surface, if a hollow bump is used it may be economical and offers other advantages over road bumps raised above the road surfaces. The method models the vehicle as the classical one-degree-of-freedom system whose base follows the road profile, approximated by Laplace Transform. Then, a traditional vibration analysis is carried out and the isolation factor is calculated. A case study application is presented to substantiate the model developed. This case indicates how much difference the current model has compared to other existing models. Therefore, a relationship is established between the characteristics of the road profile, and the vehicle vibration response. Thus, the model's impact on the vehicle speed control is specified.